2000
DOI: 10.1053/jpdn.2000.0150030
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural influences and self-care practices of middle adolescents

Abstract: The purpose of this study was to describe general self-care practices of middle adolescents. In addition, the relation between general self-care practices and specific sociocultural characteristics including socioeconomics and church attendance were explored. Orem's self-care theory and developmental theory provided the framework for the investigation. Findings from the sample of 15- and 16-year-old adolescents (n = 425) showed that they are engaging in self-care practices. The influence of sociocultural chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
2
7
1
Order By: Relevance
“…The findings showed that children with cancer and their parents were competent self-care agents, performing numerous self-care practices, consistent with previously reported research (James, 1991;Jesek-Hale, 1994;Kusaba, personal communication;Livingston, White, Ugoni, & Borland, 2001;McCaleb & Cull, 2000;McCaleb & Edgil, 1994;Moore, 1993;Moore & Mosher 1997;Mosher & Moore, 1998;Neuman, 1996). These practices were performed to meet some of the self-care requisites presented in the three major areas of universal, developmental, and health deviation (Orem, 2001).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings showed that children with cancer and their parents were competent self-care agents, performing numerous self-care practices, consistent with previously reported research (James, 1991;Jesek-Hale, 1994;Kusaba, personal communication;Livingston, White, Ugoni, & Borland, 2001;McCaleb & Cull, 2000;McCaleb & Edgil, 1994;Moore, 1993;Moore & Mosher 1997;Mosher & Moore, 1998;Neuman, 1996). These practices were performed to meet some of the self-care requisites presented in the three major areas of universal, developmental, and health deviation (Orem, 2001).…”
Section: Discussionsupporting
confidence: 88%
“…There have been many nursing studies in which researchers have investigated the self-care practices of children and adolescents (James, 1991;Jesek-Hale, 1994;Kusaba, personal communication;Livingston, White, Ugoni, & Borland, 2001;McCaleb & Cull, 2000;McCaleb & Edgil, 1994;Moore, 1993;Neuman, 1996). Fewer studies have examined selfcare practices of children with cancer and their parents (Moore & Mosher, 1997;Mosher & Moore, 1998).…”
mentioning
confidence: 99%
“…Canty-Mitchell (2001) identified a significant positive correlation between hope and self-care agency ( r = .47, p < .001). McCaleb and Cull (2000) identified a relationship between general self-care practices and church attendance ( r = . 20, p = .0001).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Previous studies proposed that self‐agency and self‐care behaviors likely increase as girls increase in age (Moore, ; Zhimin, ). However, other studies (Cull, ; Dashiff, McCaleb, & Cull, ; McCaleb & Cull, ) documented a negative correlation between age and disease‐related self‐care.…”
mentioning
confidence: 91%
“…Adolescent girls usually sought advice regarding dysmenorrhea self‐care from their mothers (Chiou & Wang, ); educated mothers may also provide detailed information regarding dysmenorrhea (Finlay, Jones, & Kreitman, ); thus, a mother's educational level possibly influenced the self‐care of adolescent girls suffering from dysmenorrhea. A father's educational level also possibly influenced self‐care (Cull, ; McCaleb & Cull, ).…”
mentioning
confidence: 99%